A case of normotensive pheochromocytoma associated with pseudotumor cerebri and uveitis - Muhsin KAYA; Dursun ARAS; Hülya ÇETİNKAYA and Kadir BAHAR and Semih AYDINTUĞ and Serpil DİZBAY SAY and Önder ALTUN and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-